Method for manufacturing electrode paste and method for manufacturing electrode
By using ultra-fine bubble water and electric field mixing, the method addresses the trade-off in electrode pastes, achieving improved electrode performance through uniform dispersibility and adsorption of ionomer and catalyst materials.
Patent Information
- Application Number
- JP2023106605
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Conventional electrode pastes face a trade-off between ionomer dispersibility and ionomer adsorption due to solvent composition, affecting electrode performance.
The method involves preparing electrode pastes using ultra-fine bubble water (UFB water) with air bubbles less than 1 μm in diameter, mixing ionomer and catalyst materials with specific solvents, and applying an electric field to enhance dispersibility and adsorption, reducing the amount of alcohol and dispersant.
This approach improves both proton and oxygen transport resistance, leading to enhanced power generation performance by ensuring uniform distribution of ionomer and catalyst materials.
Smart Images

Figure 2025006051000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an electrode paste and a method for producing an electrode. [Background technology]
[0002] For example, in electrochemical devices such as fuel cells or water electrolysis devices, the manufacturing process of electrodes has a large effect on their performance. Electrodes are generally manufactured by applying and drying an electrode paste (also called electrode ink or catalyst ink, etc.). Even when the same catalyst is used, the performance of the electrode is greatly affected by the solvent used in the electrode paste.
[0003] Non-Patent Document 1 describes how the ratio of water to alcohol affects the electrode paste solvent. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] “Investigation of the Influence of Slurry Properties and Electrode Microstructure on the Performance of Polymer Electrolyte Fuel Cell”, Michito Kishi, et.al., Journal of the Society of Powder Technology, Japan, Vol.55, 366-374, (2018) Summary of the Invention [Problem to be solved by the invention]
[0005] Conventional electrode pastes have a trade-off between the dispersibility of the ionomer and the adsorptivity of the ionomer in terms of the solvent composition, making it difficult to improve the power generation performance.
[0006] An object of the present invention is to solve the above-mentioned problems. [Means for solving the problem]
[0007] One aspect of the following disclosure is a method for producing an electrode paste, comprising: a first step of preparing a first raw material paste by mixing an ionomer, a dispersant for dispersing the ionomer, and a first solvent containing alcohol and water; a second step of preparing a second raw material paste by mixing a catalyst material, an abrasive for crushing the catalyst material, and a second solvent containing water; and a main stirring step of mixing the first raw material paste and the second raw material paste to prepare an electrode paste, wherein the first solvent and the second solvent contain ultra-fine bubble water containing bubbles having a diameter of less than 1 μm.
[0008] Another aspect is a method for manufacturing an electrode, comprising: a step of producing an electrode paste; a step of applying the electrode paste to a base material; and a step of drying the applied electrode paste, wherein the step of producing the electrode paste comprises: a first step of preparing a first raw material paste by mixing an ionomer, a dispersant for dispersing the ionomer, and a first solvent containing alcohol and water; a second step of preparing a second raw material paste by mixing a catalyst material, an abrasive for crushing the catalyst material, and a second solvent containing water; and a main stirring step of mixing the first raw material paste and the second raw material paste to prepare the electrode paste, wherein the first solvent and the second solvent contain ultra-fine bubble water containing bubbles having a diameter of less than 1 μm. Effect of the Invention
[0009] The manufacturing method of an electrode paste and the manufacturing method of an electrode from the above viewpoints can achieve both the adsorption of a catalyst material to an ionomer and the dispersibility of the ionomer, thereby improving electrode performance. [Brief description of the drawings]
[0010] [Figure 1]FIG. 1A is an explanatory diagram of a method for producing an electrode according to an embodiment, and FIG. 1B is an explanatory diagram of a first step of FIG. 1A. [Diagram 2] FIG. 2A is an explanatory diagram of the second step in FIG. 1A, and FIG. 2B is an explanatory diagram of the main stirring step in FIG. 1A. [Diagram 3] FIG. 3 is an explanatory diagram of the stirring tank in which the main stirring step of FIG. 1A is carried out. [Figure 4] FIG. 4 is a graph showing the measurement results of the alcohol fraction dependency of the ionomer adsorption rate according to the comparative example and the experimental example. [Diagram 5] FIG. 5 is an explanatory diagram of a stirring vessel according to a modified example of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As shown in FIG. 1, the manufacturing method of the electrode according to the present embodiment includes an electrode paste manufacturing step S1 (manufacturing method of the electrode paste), a coating step S2, and a drying step S3. The electrode paste manufacturing step S1 is a step of manufacturing an electrode paste by a preliminary mixing step S10 and a main mixing step S20. The electrode paste manufacturing step S1 will be described in detail later. The coating step S2 is a step of coating the electrode paste manufactured in the electrode paste manufacturing step S1 onto a predetermined substrate. The substrate is a porous gas diffusion layer, an electrolyte membrane, or a transfer sheet. The electrode paste is spread in a sheet shape by the coating step S2. The drying step S3 is a step of removing the solvent from the electrode paste formed in the coating step S2 to form a sheet-shaped electrode. The electrode manufactured in this embodiment is used, for example, in a fuel cell or a water electrolysis device.
[0012] The electrode paste is a mixture of a catalyst material in which catalyst particles are supported on a catalyst carrier, an ionomer (e.g., a proton-conductive ion exchange resin), a solvent, and additives (dispersing agents and abrasives). Immediately after the application step S2, the catalyst material and the ionomer are dispersed in the solvent. In a conventional electrode paste, the solvent contains water and alcohol in a predetermined ratio. The solvent is removed in the drying step S3. In the initial stage of the drying step S3, the evaporation of relatively volatile components of the solvent, such as alcohol, proceeds preferentially. As the solvent evaporates, the distance between the catalyst materials and the distance between the catalyst material and the ionomer decreases. In addition, a surface concentration layer in which the concentration of the catalyst material is locally increased is formed on the surface of the electrode paste. As the evaporation proceeds, the aggregation of the catalyst material proceeds, and the distance between the catalyst materials increases again. Some of the ionomer aggregates in layers on the surface.
[0013] As the drying step S3 progresses, the water remaining in the solvent evaporates. As a result, the ionomer is adsorbed onto the surface of the catalyst material, and the ionomer coats the surface of the catalyst material. As the water evaporates, an electrode is completed in which the ionomer and catalyst material are entangled in a network shape.
[0014] In the above-mentioned electrode paste, if the ratio of water in the solvent is high, the dispersion of the ionomer is poor and the ionomer remains in the electrode paste as relatively large lumps. When such an electrode paste is dried, the surface of the catalyst material is covered with a thick layer of ionomer. In such an electrode, protons can easily move through the ionomer, so the proton transport resistance is reduced. However, the oxygen transport path to the catalyst material is reduced, so the oxygen transport resistance increases.
[0015] On the other hand, when the proportion of alcohol in the solvent in the electrode paste is high, the affinity between the ionomer and the solvent increases, and the ionomer can be dispersed in a fine state. However, in such an electrode paste, the surface of the ionomer is left covered with alcohol molecules in the drying step S3. Such an ionomer has low adsorption to the catalyst material, and the amount of it adsorbed on the surface of the catalyst material is reduced. As a result, the resulting electrode has a limited proton migration path to the catalyst material, which increases the proton transport resistance.
[0016] Furthermore, in the drying step S3, problems occur in the conventional electrode paste due to the difference in volatility between the alcohol and water in the solvent, which causes the distribution of the catalyst material and ionomer to be non-uniform in the thickness direction of the electrode, preventing the uniformity of the composition and microstructure.
[0017] Therefore, in this embodiment, ultra-fine bubble water (hereinafter referred to as UFB water) is used as a solvent for the electrode paste. The preliminary mixing step S10 in this embodiment includes a first step S110 (see FIG. 1B) of dispersing an ionomer in a solvent, and a second step S120 (see FIG. 2A) of dispersing a catalyst material in the solvent.
[0018] As shown in FIG. 1B, the first step S110 includes a first solvent preparation step S111. The first solvent preparation step S111 is a step of preparing a first solvent by mixing an alcohol with the first UFB water. The alcohol may be, for example, any one of methanol, ethanol, normal propanol, and isopropanol, or a combination thereof. Here, the alcohol may be, for example, normal propanol (NPA). The alcohol attaches to the surface of the ionomer molecules, increases the absolute value of the zeta potential of the ionomer, and stabilizes the dispersion state in the solvent.
[0019] The UFB water is water (e.g., pure water) containing bubbles less than 1 μm in diameter. In this embodiment, UFB water of different conditions is used in the first step S110 (FIG. 1B) and the second step S120 (FIG. 2A). The UFB water used in the first step S110 is first UFB water. The first UFB water contains bubbles less than 1 μm in diameter at a concentration of about 500 million / ml or more and less than about 1 billion / ml. The first UFB water has better wettability with respect to ionomer and catalyst materials than pure water.
[0020] Next, the first step S110 proceeds to the vibration stirring step S112. In the vibration stirring step S112, the first UFB water and the alcohol are uniformly mixed by vibration stirring for about several minutes, and the preparation of the first solvent is completed. The first UFB water after the vibration stirring step S112 has a pH value of 6.5 to 7.5, air bubbles have a diameter of about 90 to 110 nm, and the zeta potential of the air bubbles is about -60 mV.
[0021] Next, the first step S110 proceeds to an ionomer introduction step S113. In the ionomer introduction step S113, an ionomer, an alcohol, a dispersant, and a first UFB water are introduced into a first solvent. The ionomer is a polymer electrolyte material having proton conductivity, and for example, "Nafion" (registered trademark) manufactured by DuPont can be used. The dispersant is a substance that adheres to the molecules of the ionomer to facilitate dispersion of the ionomer in the first solvent. The dispersant may be a surfactant or an alcohol. The ionomer is introduced into the first solvent in a state where it is mixed with the alcohol, the dispersant, and the first UFB water. The first solvent after introduction or stirring of the ionomer has a pH value of 2.5 to 3.5, a bubble diameter of about 190 to 440 nm, and a zeta potential of about -10 mV.
[0022] The first UFB water has a zeta potential that matches the affinity of the ionomer, making it easy to disperse the ionomer. In this embodiment, the first UFB water has a large absolute value of the zeta potential, so the dispersibility of the ionomer is improved. Therefore, the amount of alcohol and dispersant for dispersing the ionomer can be reduced more than in the past. In some embodiments, the ionomer may be dispersed using only the first UFB water without using alcohol and dispersant.
[0023] After that, the first step S110 proceeds to a stirrer stirring step S114. In the stirrer stirring step S114, the first raw material paste is stirred by a stirrer. The stirrer stirring step S114 is performed, for example, for several tens of minutes to several hours. The stirrer stirring step S114 disperses the ionomer in the first solvent. In this embodiment, the ionomer can be efficiently dispersed by using UFB water, which has a larger absolute value of the zeta potential than pure water. Therefore, the amount of alcohol and dispersant added to the first raw material paste can be suppressed or reduced. Suppressing the amount of alcohol and dispersant added that do not contribute to the electrode reaction contributes to improving the performance of the electrode. Through the above steps, the first step S110 is completed, and a first raw material paste in which the ionomer is dispersed in the first solvent is produced.
[0024] The first raw material paste has a pH value of 2.5 to 3.5 and a zeta potential of -3 to -18 mV. The diameter of the bubbles contained in the first raw material paste is approximately 190 to 440 nm.
[0025] As shown in FIG. 2A, the second step S120 is a step of dispersing the catalyst material in the second solvent to prepare a second raw material paste. The second step S120 first includes a catalyst introduction step S121 in which the catalyst material and the abrasive are introduced into a predetermined stirring vessel. The catalyst material is, for example, a carrier carrying a catalyst. The catalyst may be, for example, any of platinum group elements (platinum, palladium, ruthenium, iridium, rhodium, osmium), iron, lead, copper, chromium, cobalt, nickel, manganese, vanadium, and molybdenum, or an alloy thereof. The carrier may be, for example, any of activated carbon, carbon black, porous carbon, and carbon nanotubes, or a mixture thereof.
[0026] The abrasive is abrasive beads, which are granular bodies harder than the carrier. The abrasive is added to break down the agglomerated catalyst material. The abrasive beads include, for example, ceramic materials such as alumina, zirconia, or silica.
[0027] Next, the second step S120 proceeds to a first vibration and stirring step S122. The catalyst material and the polishing beads are mixed by the first vibration and stirring step S122. The processing time of the first vibration and stirring step S122 may be a relatively short time of about several seconds to several tens of seconds.
[0028] Next, the second step S120 proceeds to a UFB water introduction step S123 in which second UFB water is introduced. The second UFB water used in the second step S120 is water containing bubbles with a diameter of less than 1 μm at a concentration of about 1 billion bubbles / ml or more. The second UFB water has the same pH value as the first UFB water and the same zeta potential as the first UFB water. The contact angle of the second UFB water decreases as the bubble concentration increases. The second UFB water has a lower contact angle and better wettability than the first UFB water. The diameter of the bubbles in the second UFB water (and the first UFB water) changes according to the pH value of the water when the adjustment is performed. The lower the pH value, the larger the diameter of the bubbles obtained.
[0029] Next, the second step S120 proceeds to a second vibration stirring step S124. In the second vibration stirring step S124, stronger vibrations than those in the first vibration stirring step S122 are applied to the mixture of the second UFB water, the catalyst material, and the polishing beads. In the second vibration stirring step S124, the second UFB water, which has excellent wettability, penetrates into the gaps between the particles of the aggregated catalyst material, and displaces and removes the liquid and gas (e.g., air) adsorbed on the surface of the catalyst material, causing the aggregates of the catalyst material to become swollen. In addition, the impact (cavitation effect) caused when the high concentration of bubbles contained in the second UFB water bursts and disappears promotes the pulverization of the aggregates of the catalyst material. The second UFB water contains a high concentration of very fine bubbles with a diameter of about 90 to 110 nm, so that the inside of the aggregated catalyst material can be washed more finely.
[0030] Through the above steps, the second raw material paste is prepared, and the second step S120 is completed. The second raw material paste has a pH value of 6.5 to 7.5 and a zeta potential of -59 to -74 mV. The diameter of the bubbles contained in the second raw material paste is about 90 to 110 nm.
[0031] Next, a main stirring step S20 shown in Fig. 2B is performed. The main stirring step S20 is performed using a stirring tank 20 shown in Fig. 3. The stirring tank 20 has a container body 22, a stirring member 24, and a plurality of electrode plates 26 (electrodes). The container body 22 is a container capable of containing the first raw material paste and the second raw material paste, and contains the stirring member 24 therein. The container body 22 is preferably formed of a dielectric material (insulating material) so as to pass the electric field of the electrode plates 26.
[0032] The stirring member 24 is a member that mechanically stirs the first raw material paste and the second raw material paste that are put inside. The stirring member 24 may be a stirring propeller 28 equipped with a plurality of stirring blades as shown in the figure. The stirring member 24 is not limited to a stirring propeller. The stirring member 24 may be a rotor that rotates in a predetermined direction and rotates the surrounding liquid.
[0033] The electrode plate 26 is attached to the outer periphery of the container body 22. Two (a pair) or more electrode plates 26 are arranged on the outer periphery of the container body 22, spaced apart in the circumferential direction. The electrode plates 26 generate a horizontal electric field between each other. The electric field generated between the electrode plates 26 passes through the container body 22. As a result, the electrode plates 26 apply an electric field to the liquid inside the container body 22. The electric field generated by the electrode plates 26 can drive negatively charged fine bubbles (ultra-fine bubbles) by electrophoresis. In this embodiment, the movement of the bubbles by electrophoresis can effectively generate cavitation of the bubbles, promoting the crushing of secondary particles of the catalyst material and lumps of the ionomer.
[0034] 2B, the main stirring step S20 proceeds to a raw material input step S201. In the raw material input step S201, the first raw material paste, the second raw material paste, and the second UFB water are input into the stirring tank 20. The second UFB water used in the raw material input step S201 is water containing bubbles with a diameter of less than 1 μm at a concentration of about 1 billion bubbles / ml or more.
[0035] Next, the main stirring step S20 proceeds to a bead mill stirring step S202. In the bead mill stirring step S202, the first raw material paste, the second raw material paste, and the second UFB water are stirred in the presence of abrasives (beads) by the stirring member 24 of the stirring tank 20. In addition, the multiple electrode plates 26 drive the bubbles by electrophoresis. The driving direction of the bubbles can be switched in a short time to the same direction or the opposite direction to the flow direction of the liquid inside the stirring tank 20.
[0036] In the bead mill stirring step S202, the second UFB water, which has excellent wettability, can penetrate into the fine gaps between the secondary particles of the catalyst material, causing the secondary particles to become swollen. Such catalyst material is easily crushed by the polishing beads and separated into primary particles. Furthermore, bubbles driven by electrophoresis cause cavitation (a crushing effect due to bursting) inside or near the catalyst material, promoting the crushing of the secondary particles of the catalyst material. The bubbles contained in the first UFB water and the second UFB water are as fine as about 90 to 110 nm, so they can enter the fine gaps between the aggregated catalyst material and crush the catalyst material more finely. Therefore, the catalyst material can be crushed more finely than when only polishing beads are used.
[0037] After that, the main stirring step S20 proceeds to the adjustment step S203. In the adjustment step S203, the first UFB water is charged into the stirring tank 20. In the adjustment step S203, the disintegration has progressed sufficiently and further disintegration is not necessary, so the first UFB water containing about 500 million bubbles / ml is used. The first UFB water in this step is charged to make a final adjustment to the dispersion state. The pH value of the first UFB water in the adjustment step S203 is adjusted to 6.5 to 7.5, the zeta potential is about -60 mV, and the diameter of the bubbles is about 90 to 110 nm. The first UFB water charged in the adjustment step S203 optimizes the zeta potential of the catalyst material and ionomer of the electrode paste and prevents re-aggregation of the ionomer and catalyst material.
[0038] Through the above steps, the main stirring step S20 is completed, and the electrode paste is completed. After the main stirring step S20 is completed, the electrode paste has a pH value of 2.5 to 3.5, a zeta potential of the bubbles is about -10 mV, and a diameter of the bubbles is about 190 to 440 nm. The electrode paste of this embodiment can reduce or eliminate the amount of alcohol and dispersant added.
[0039] In addition, since the electrode paste of the present embodiment uses the first UFB water and the second UFB water, which have excellent dispersibility, as the solvent, the ionomer and the catalyst material can be kept finely dispersed while suppressing the amount of alcohol and dispersant. Such an electrode paste has a low affinity between the solvent and the ionomer. That is, there is little material that continues to adsorb around the ionomer and prevents the ionomer from adsorbing to the catalyst material. Therefore, in the electrode paste of the present embodiment, in the drying step S3, the finely dispersed ionomer can adhere to the catalyst material in a sufficient amount while maintaining the oxygen diffusion path. As a result, the electrode paste of the present embodiment can simultaneously improve the proton transport resistance and the oxygen transport resistance, and can improve the power generation performance when used in, for example, a fuel cell.
[0040] The alcohol and dispersing agent are adsorbed and remain on the surface of the catalyst material, and may generate residual acid that reduces the activity of the electrode when oxidized. The electrode paste of the present embodiment can prevent the performance of the electrode from decreasing by reducing or eliminating the amount of the alcohol and dispersing agent added.
[0041] In addition, the electrode paste of the present embodiment has a more uniform solvent composition than the conventional one due to the reduced alcohol content, which results in the suppression of uneven composition in the sheet-shaped electrode paste in the drying step S3, and allows the formation of an electrode layer in which the ionomer and catalyst material are more uniformly dispersed in the thickness direction.
[0042] (Experimental Example) The results of evaluating the mixed state of the electrode paste are described below. In this experimental example, evaluation was performed using the electrode paste according to the present embodiment, which uses alcohol and UFB water as a solvent, and the electrode paste according to the comparative example, which uses alcohol and water as a solvent.
[0043] In this experimental example and comparative example, an experiment was conducted to quantify the adsorption rate of the ionomer on the surface of the catalyst support by changing the alcohol fraction in the solvent. Centrifugal treatment was used to quantify the amount of ionomer adsorbed on the surface of the catalyst support. Centrifugal treatment of the electrode paste (ink) in which the catalyst support is dispersed forces the ionomer adsorbed on the catalyst surface to settle together with the catalyst. Therefore, the supernatant contains only the ionomer that was not involved in adsorption on the catalyst surface. The amount of ionomer remaining in the supernatant was quantified, and the amount of ionomer in the supernatant was subtracted from the amount charged, to quantify the amount of ionomer adsorbed (and adsorption rate).
[0044] The results of this experimental example are shown in FIG. 4. As shown in the figure, both the experimental example and the comparative example show a tendency for the adsorption rate of the ionomer to increase as the alcohol content in the solvent decreases. When comparing the experimental example and the comparative example at the same alcohol content, the comparative example has a higher adsorption rate of the ionomer. However, in the comparative example, when the alcohol content falls below a certain value, the catalyst support (carbon support) aggregates. Therefore, a stable electrode paste can only be obtained within a certain range of alcohol content, which results in a restriction of the adsorption rate of the ionomer.
[0045] On the other hand, the electrode paste of this experimental example, which used UFB water, was able to prevent the aggregation of the catalyst support (carbon support) even at a lower alcohol content range than the comparative example. Furthermore, at a lower alcohol content range, the adsorption rate of the ionomer was increased more than in the comparative example, confirming the superiority of the lower alcohol content range.
[0046] The above results are believed to be due to the fact that by changing from water to UFB water, the absolute value of the zeta potential increases, and UFB water, which has the effect of improving dispersion function, plays a role similar to that of alcohol. The results of this experimental example show that even when ionomer adsorption performance is improved with a solvent with a low alcohol fraction, it is possible to prevent the occurrence of agglomeration of the catalyst support and improve the trade-off between ionomer adsorption and dispersibility.
[0047] (Modification of the embodiment) The stirring tank 20A according to this modified example will be described below. The stirring tank 20A according to this modified example shown in Fig. 5 can be used in place of the stirring tank 20 (Fig. 3) in the main stirring step S20 (Fig. 2B). Note that the same components in the stirring tank 20A as those in the stirring tank 20 are denoted by the same reference numerals, and detailed descriptions thereof will be omitted.
[0048] The stirring tank 20A includes a vessel body 22, a stirring member 24A, and an electrode plate 26A. The stirring member 24A includes two stirring propellers 28, 28a (rotating blades). The two stirring propellers 28, 28a are arranged vertically apart from each other and can rotate in different directions. The electrode plate 26A is attached to the upper stirring propeller 28 and the lower stirring propeller 28a. These electrode plates 26A generate an electric field in the vertical direction between the two stirring propellers 28, 28a. The electrode plate 26A can drive fine bubbles in the vertical direction by electrophoresis.
[0049] The stirring tank 20A of this modified example can more efficiently stir the catalyst material and the ionomer in the main stirring step S20 by electrophoresing fine bubbles in the vertical direction.
[0050] In addition to the above disclosure, the following notes are also disclosed.
[0051] (Appendix 1) One aspect is a method for producing an electrode paste, comprising a first step (S110) of preparing a first raw material paste by mixing an ionomer, a dispersing agent for dispersing the ionomer, and a first solvent containing alcohol and water, a second step (S120) of preparing a second raw material paste by mixing a catalyst material, an abrasive for crushing the catalyst material, and a second solvent containing water, and a main stirring step (S20) of mixing the first raw material paste and the second raw material paste to prepare an electrode paste, in which the first solvent and the second solvent contain ultra-fine bubble water containing bubbles with a diameter of less than 1 μm. This method for producing an electrode paste uses ultra-fine bubble water (UFB water) with excellent dispersibility, thereby making it possible to disperse aggregated catalyst material and ionomer more finely. In addition, the amount of alcohol and dispersing agent added to improve dispersibility can be suppressed, so that the average molecular weight of the solvent is reduced and wettability is also improved. As a result, in the main stirring step, the decrease in dispersibility of the catalyst material is suppressed. Furthermore, by reducing the amount of alcohol and dispersant, the generation of residual acids (such as propionic acid) that may deteriorate electrode performance over the long term can be reduced, making it possible to produce electrodes with excellent durability.
[0052] (Appendix 2) In the method for producing an electrode paste according to Appendix 1, the first raw material paste may have a pH value of about 2.5 to about 3.5. In the method for producing an electrode paste, when the ionomer is dispersed in the first solvent, the surface of the ionomer can be maintained at a zeta potential suitable for dispersion, improving the dispersibility of the ionomer.
[0053] (Appendix 3) In the method for producing an electrode paste according to Appendix 2, the first raw material paste may have a zeta potential of about -3 to about -18 mV. In such a method for producing an electrode paste, the ionomer can be suitably dispersed when dispersing the ionomer in the first solvent.
[0054] (Appendix 4) In the electrode paste manufacturing method according to Appendix 1, the second raw material paste may have a pH value of about 6.5 to about 7.5. According to this electrode paste manufacturing method, electrophoresis of bubbles can be caused at an appropriate value, so that the dispersibility in the main stirring step can be improved and the processing time of the main stirring step can be shortened. In addition, the electrode paste manufacturing method can reduce the amount of abrasive used to crush secondary particles of the catalyst material.
[0055] (Appendix 5) In the electrode paste manufacturing method according to appended claim 4, the second raw material paste may have a zeta potential of about -59 to about -74 mV. This electrode paste manufacturing method can shorten the processing time of the main stirring step by improving the dispersibility in the main stirring step. Also, this electrode paste manufacturing method can reduce the amount of abrasive used to crush secondary particles of the catalyst material.
[0056] (Appendix 6) In the method for producing an electrode paste according to any one of Supplementary Notes 1 to 5, the diameter of the bubbles contained in the ultra-fine bubbled water in the first raw material paste may be about 190 to about 440 nm, and the diameter of the bubbles contained in the ultra-fine bubbled water in the second raw material paste may be about 90 to about 110 nm. In this method for producing an electrode paste, the cavitation effect of the bubbles is appropriately generated, thereby making it possible to further efficiently disperse the catalyst material and the ionomer.
[0057] (Appendix 7) In the method for producing an electrode paste according to any one of Supplementary Notes 1 to 6, the main stirring step may be performed using a stirring tank (20, 20A) having a plurality of electrodes that apply an electric field to the liquid and a stirring member (24, 24A) that mechanically causes the liquid to flow. According to this method for producing an electrode paste, by applying an electric field that causes electrophoresis in the same direction as or opposite to the rotation direction of the stirring member, it is possible to promote the exertion of the cavitation effect of the bubbles, and further promote the mixing of the catalyst material and the ionomer.
[0058] (Appendix 8) In the method for producing an electrode paste according to Appendix 7, the electrodes in the stirring tank may generate an electric field in a horizontal direction. In this method for producing an electrode paste, the bubbles are driven by electrophoresis in the horizontal direction, thereby promoting mixing of the catalyst material and the ionomer.
[0059] (Appendix 9) In the method for producing an electrode paste according to appended claim 7, the stirring member may include a plurality of rotors or rotor blades arranged at intervals in the vertical direction, and the plurality of electrodes may generate an electric field in the vertical direction. According to this method for producing an electrode paste, the bubbles are driven by electrophoresis in the vertical direction, thereby further improving dispersibility.
[0060] (Appendix 10) In the method for producing an electrode paste according to any one of Supplementary Note 1 to 9, the ultra-fine bubbled water used in the first solvent and the ultra-fine bubbled water used in the second solvent may be adjusted to a pH value of about 6.5 to about 7.5. This method for producing an electrode paste can more finely disperse aggregated catalyst material and ionomer.
[0061] (Appendix 11) In the method for producing an electrode paste according to any one of Supplementary Note 1 to 10, the ultra-fine bubble water used in the first solvent may contain bubbles having a diameter of less than 1 μm at a concentration of about 500 million bubbles / ml or more. According to this method for producing an electrode paste, a first raw material paste in which an ionomer is suitably dispersed can be obtained.
[0062] (Appendix 12) In the method for producing an electrode paste according to any one of Supplementary Note 1 to 11, the ultra-fine bubble water used in the second solvent may contain bubbles having a diameter of less than 1 μm at a concentration of about 1 billion bubbles / ml or more. According to this method for producing an electrode paste, the catalyst material can be efficiently dispersed in the main stirring step.
[0063] (Appendix 13) Another aspect is a method for producing an electrode, comprising: a step of producing an electrode paste, a coating step (S2) of coating the electrode paste on a substrate, and a step of drying the coated electrode paste, the step of producing the electrode paste comprising: a first step of mixing an ionomer, a dispersing agent for dispersing the ionomer, and a first solvent containing alcohol and water to prepare a first raw material paste, a second step of mixing a catalyst material, an abrasive for crushing the catalyst material, and a second solvent containing water to prepare a second raw material paste, and a main stirring step of mixing the first raw material paste and the second raw material paste to prepare the electrode paste, the first solvent and the second solvent containing ultra-fine bubble water containing bubbles with a diameter of less than 1 μm. Such an electrode production method can achieve both the adsorption of the ionomer to the catalyst material and the dispersibility of the ionomer.
[0064] The present invention is not limited to the above disclosure, and various configurations can be adopted without departing from the gist of the present invention. [Explanation of symbols]
[0065] 20, 20A...Stirring tank 22...Container body 24, 24A... Stirring member 26, 26A... Electrode plate 28, 28a…Agitating propeller
Claims
1. A first step of preparing a first raw material paste by mixing an ionomer, a dispersing agent for dispersing the ionomer, and a first solvent containing alcohol and water; A second step of preparing a second raw material paste by mixing a catalyst material, an abrasive for crushing the catalyst material, and a second solvent containing water; A main stirring process of mixing the first raw material paste and the second raw material paste to prepare an electrode paste, The method for producing an electrode paste, wherein the first solvent and the second solvent contain ultra-fine bubble water containing bubbles having a diameter of less than 1 μm.
2. 2. The method for producing an electrode paste according to claim 1, wherein the pH value of the first raw material paste is 2.5 to 3.
5.
3. 3. The method for producing an electrode paste according to claim 2, wherein the first raw material paste has a zeta potential of −3 to −18 mV.
4. 2. The method for producing an electrode paste according to claim 1, wherein the pH value of the second raw material paste is 6.5 to 7.
5.
5. 5. The method for producing an electrode paste according to claim 4, wherein the second raw material paste has a zeta potential of −59 to −74 mV.
6. 2. The method for producing an electrode paste according to claim 1, wherein the diameter of bubbles contained in the ultra-fine bubbled water in the first raw material paste is 190 to 440 nm, and the diameter of bubbles contained in the ultra-fine bubbled water in the second raw material paste is 90 to 110 nm.
7. 2. The method for producing an electrode paste according to claim 1, wherein the main stirring step is performed using a stirring tank having a plurality of electrodes that apply an electric field to the liquid and a stirring member that mechanically causes the liquid to flow.
8. 8. The method for producing an electrode paste according to claim 7, wherein the electrodes in the stirring tank generate an electric field in a horizontal direction.
9. 8. The method for producing an electrode paste according to claim 7, wherein the stirring member comprises a plurality of rotors or rotor blades arranged at intervals in the vertical direction, and the plurality of electrodes generate an electric field in the vertical direction.
10. 2. The method for producing an electrode paste according to claim 1, wherein the ultra-fine bubbled water used in the first solvent and the ultra-fine bubbled water used in the second solvent are adjusted to a pH value of 6.5 to 7.
5.
11. 2. The method for producing an electrode paste according to claim 1, wherein the ultra-fine bubble water used in the first solvent contains bubbles having a diameter of less than 1 μm at a concentration of 500 million bubbles / ml or more.
12. 12. The method for producing an electrode paste according to claim 1, wherein the ultra-fine bubble water used in the second solvent contains bubbles having a diameter of less than 1 μm at a concentration of 1 billion bubbles / ml or more.
13. Producing an electrode paste; A coating step of coating the electrode paste onto a substrate; and drying the applied electrode paste. The step of producing the electrode paste includes: A first step of preparing a first raw material paste by mixing an ionomer, a dispersing agent for dispersing the ionomer, and a first solvent containing alcohol and water; A second step of preparing a second raw material paste by mixing a catalyst material, an abrasive for crushing the catalyst material, and a second solvent containing water; A main stirring process of mixing the first raw material paste and the second raw material paste to prepare the electrode paste, The method for manufacturing an electrode, wherein the first solvent and the second solvent contain ultra-fine bubble water containing bubbles having a diameter of less than 1 μm.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery and its manufacturing method
JP2002298922A
Electrode / polymer electrolyte assembly and fuel cell
JP2008016270A
Method for manufacturing electrode paste
JP2011014334A
Ionomer-modified hydrophobic particles, catalyst layer, and catalyst ink and method for producing the same
JP2022173720A
Battery electrode forming method, manufacturing method for membrane electrode assembly, membrane electrode assembly, and fuel cell or water electrolysis hydrogen generating device
JP2023044167A